Relationships at School: External Evaluation Angle - Martišauskienė, Elvyda; Vaičekauskienė, Snieguolė (Pedagogika, 2016)
A humane relationships at school develop favourable micro-climate for learning, promote good student behaviour, learning motivation and provides the right conditions for becoming a mature personality. For this research external evaluation data from schools of general education collected by the National Agency for School Evaluation in 2012 was used. This paper analyses students’, parents’ and external evaluators’ approaches and discusses the relationships in the modern school – situation and expression; highlights the most important trends in the relationships, relevant to all members of the school community; raises actual educational problems. Sociologists and educationists recognize that the nature of the relationships depends on a person’s self-determination, which is based on their perceived motives, beliefs, values and attitudes. Study data also shows that good relationships are influenced by the teacher’s personality and competencies: strictness, properly organized educational process with emotional basis and respect for the student; the school context: social, economic, cultural, educational school environment and prevailing micro-climate. The study also highlights the fact that students and their parents differently rate relationships at school: prevailing relationships at school usually satisfies parents and are evaluated positively, however, students believe that the school can achieve better (especially at 5–8 grades lessons). Schools focus on moral community relations, but still occur simulation, activities and behaviour that encourage alienation. External evaluation data shows that high student performance, achievements, knowledge is often considered to be the most important, however education of moral values, humane relationships – less significant thing. In schools of general education dominate business like and interpersonal relationships. Transcendental school community relations (the ability to go deep into yourself and others, rely on the phenomenon of conscience, overstep yourself) are aspirational so far.